A new xanthone from Garcinia nitida - Ee, Gwendoline Cheng Lian; Foo, C. H.; Jong, Vivien Yi Mian; Ismail, Nor Hadiani; Md. Sukari, Mohd Aspollah; Yap, Taufiq Yun Hin; Awang, Khalijah (Taylor & Francis, 2012)
A detailed chemical study on the stem bark of Garcinia nitida has led to the isolation of five xanthones. They are 1,6-dihydroxy-5-methoxy-6, 6-dimethylpyrano[2',3':2,3]-xanthone (1), inophyllin B (2), osajaxanthone (3), 3-isomangostin (4) and rubraxanthone (5). The structures of these compounds were established using mainly 1-D and 2-D NMR spectroscopy (1H, 13C, DEPT, COSY, HMBC and HMQC) while molecular masses were determined via MS techniques; 1 is a new compound.